Piperine regulates the circadian rhythms of hepatic clock gene expressions and gut microbiota in high-fat diet-induced obese rats - Weiyun Zhang; Chi-Tang Ho; Wenlian Wei; Jie Xiao; Muwen Lu (Food Science and Human Wellness)
The interplay between the host circadian clock and microbiota has significant influences on host metabolism processes, and circadian desynchrony triggered by high-fat diet (HFD) is closely related to metabolic disorders. In this study, the modulatory effects of piperine (PIP) on lipid metabolism homeostasis, gut microbiota community and circadian rhythm of hepatic clock gene expressions in obese rats were investigated. The Sprague-Dawley (SD) rats were fed with normal diet (ND), HFD and HFD supplemented with PIP, respectively. After 9 weeks, rats were sacrificed with tissue and fecal samples collected for circadian analysis. Results showed that chronic PIP administration ameliorated the obesity-induced alterations in lipid metabolism and dysregulation of hepatic clock gene expressions in obese rats. The gut microbial communities studied through 16S rRNA sequencing showed that PIP ameliorated the imbalanced microbiota and recovered the circadian rhythm of Lactobacillaceae, Desulfovibrionaceae, Paraprevotellaceae, and Lachnospiraceae. The fecal metabolic profiles indicated that 3-dehydroshikimate, cytidine and lithocholyltaurine were altered, which were involved in the amino acid and fatty acid metabolism process. These findings could provide theoretical basis for PIP to work as functional food to alleviate the lipid metabolism disorder, circadian rhythm misalignment, and gut microbiota dysbiosis with wide applications in the food and pharmaceutic industries.